2007
DOI: 10.1080/09540120600983971
|View full text |Cite
|
Sign up to set email alerts
|

It's not just what you say: Relationships of HIV dislosure and risk reduction among MSM in the post-HAART era

Abstract: In the post-HAART era, critical questions arise as to what factors affect disclosure decisions and how these decisions are associated with factors such as high-risk behaviors and partner variables. We interviewed 1,828 HIV-positive men who have sex with men (MSM), of whom 46% disclosed to all partners. Among men with casual partners, 41.8% disclosed to all of these partners and 21.5% to none. Disclosure was associated with relationship type, perceived partner HIV status and sexual behaviors. Overall, 36.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 24 publications
1
56
2
1
Order By: Relevance
“…Men reporting higher vengefulness might have been more reticent about their HIV serostatus due to the reasons suggested by previous research into disclosure. That is, vengefulness might have intrinsic properties that manifest as apathetic behavior towards others (i.e., nondisclosure; Stuckless and Goranson 1992); or social proximity and relationship type might be factors that are particularly germane to vengeful individuals and their decisions to disclose (Hart et al 2005;Klitzman et al 2007). These previously researched factors might even be interacting with the feelings of justice and health equity restitution possibly derived from not disclosing one's serostatus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Men reporting higher vengefulness might have been more reticent about their HIV serostatus due to the reasons suggested by previous research into disclosure. That is, vengefulness might have intrinsic properties that manifest as apathetic behavior towards others (i.e., nondisclosure; Stuckless and Goranson 1992); or social proximity and relationship type might be factors that are particularly germane to vengeful individuals and their decisions to disclose (Hart et al 2005;Klitzman et al 2007). These previously researched factors might even be interacting with the feelings of justice and health equity restitution possibly derived from not disclosing one's serostatus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, instances in which significant results have been found linking anger (Marks et al 1998) and hostility (Perkins et al 1993) in MSM with unprotected anal intercourse were not replicable in later work (Kalichman 1999). Additionally, recent studies show that risk-taking behaviors and HIV disclosure may be more a result of partner type, perceived seroconcordance, and enacted sexual behaviors rather than negative affect or traits (Hart et al 2005;Klitzman and Bayer 2003;Klitzman et al 2007). Thus, the utility of vengeance as a predictor of condom use, disclosure, or other instances of risk-taking behavior may be equally questionable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While on the one hand Parsons and his team (2003) argue that increased disclosure is indeed associated with a reduction in sexual risk behaviour, on the other hand Crepaz and Marks (2003) have shown that disclosure does not always alter risk taking behaviours since, according to them, even with disclosure, unsafe sex sometimes occurs. Furthermore, some people engage in safer sex behaviours even without discussion of HIV status (Klitzman et al 2007).…”
Section: Disclosure and Social Relationshipsmentioning
confidence: 99%
“…Seropositive disclosure is often inconsistent [36][37][38][39][40][41] ; varies by partner type (with less disclosure to casual sex partners than to steady partners) 36,39,40,[42][43][44] ; is inversely related to the number of sex partners 37 ; and is less likely to occur if the sexual partner's serostatus is negative or unknown rather than positive. 45 A review of 23 empirical studies through 2004 failed to establish a consistent relationship between disclosure and safer sex.…”
mentioning
confidence: 99%